Glow and Lovely: #x2018;Old Wine in a New Bottle#x2019; (Global Journal of Management and Business Research, 2021)
Cosmetic companies like Unilever sell the perception of general people about beauty through their advertisements and reinforce it to promote their business. Even they do it in disguise form using a positive name and without changing any content in advertisements. By using qualitative semiotic analysis, this research shows how fair-skinned models, white color, and white light are used in the advertisements of Unilever#x2019;s recently name changed product #x201C;Glow and Lovely#x201D; on Bangladeshi TV channels. In the ads of it, any darkness on the skin is shown as unexpected and a hindrance to beauty, success, empowerment, and equality. All of these contents promote fairness as beauty and sustain discrimination based on skin color in society. The research also reveals a close relationship between the perceptions of general people about beauty and the meanings of the #x2018;signs#x2019; used in the sampled advertisements.